When I feel that I am better off, science seems to make the world better off too: inequality, perceived standard of living and perceptions toward science - Han, Seungwoo; Lee, Yookyung (Frontiers in Psychology, 2023)
The COVID-19 pandemic has underscored that divisive views on science and technology span both the Global North and South. This study posits that an individual’s perception of their current living standard acts as a mediating factor linking income inequality to attitudes towards scientific and technological advancements. It contends that rising income disparities shape perceptions, making individuals feel their current living conditions have not surpassed those of prior generations. Consequently, such perceptions diminish the likelihood of recognizing the positive impacts of science and technology on societal progress and future prospects. This paper sheds light on how escalating inequality fosters societal rifts concerning science and technology.